Gambaran Erupsi Gigi Permanen pada Anak Sindrom Down Usia 10-16 Tahun di Sekolah Luar Biasa Kabupaten Jember - Sinaga, Loly Anastasya; Apriyono, Dwi Kartika; Novita, Masniari (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 8 No 1 (2018): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2018.v08.i01.p02, 2018)
Background : Down Syndrome is a genetic disorder that occurs because of chromosome 21 has three chromosome (trisomy 21). The extra chromosome changes the genetic balance, physical characteristic, intellectual abilities, and physiological body function. Tooth eruption in Down Syndrome children typically delayed in both the timing and sequence of eruption up to two or three years. Objective : To observe the permanent teeth eruption in Down syndrome children at age 10-16 years old, boys and girls in Special Needs School in Jember. Materials and Methods : This research was a descriptive study with 7 subjects. Each subject was examined then calculated teeth that had emerged or functionally eruption with articualting paper. Result and Conclusion :  Both permanent teeth that is still partially erupted tooth (emerged/ EM) and had erupted perfectly (functionally eruption/ FE) delayed in eruption in Down Syndrome boys and girls at age 10-16 years old.